Comparative Study of Antibacterial and Cytotoxic Activity of Two Nepalese Medicinal Plants- Allium wallichii Kunth and Allium sativum L. - Gyawali, Dr. Rajendra (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACTAntimicrobial and cytotoxic activity of methanolic extract of two Nepalese species Allium wallichii Kunth and Allium sativum L has been evaluated. Phytochemical screening revealed the presence of terpenoids, flavanoids and reducing sugars as main phytochemical groups. The extracts screened for their antimicrobial activity on eight different strains of human pathogenic microorganisms; Escherichia coli, Salmonella typhi, Salmonella paratyphi, Pseudomonas species, Staphylococcus aureus, Klebsiella pneumoniae, Enterococcus faecalis and Klebshiella oxytoca has shown selected antimicrobial effects. LC50 values were calculated by using brime shrimp lethality test. The LC50 value for Allium wallichii Kunth was 64.714 ppm while for Allium sativum L it was found to be 172.48 ppm.